3D printing of architectured epoxy-based composite lattices with exceptional strength and toughness. (1st May 2023) - Wang, Zhenyu; Zhang, Xingle; Cheng, Changli; Liu, Yanjun; Qu, Daopeng; Shao, Pengpeng; Jiang, Jing; Liu, Yu
Abstract: Due to the exceptional mechanical properties, epoxy-based composites have been widely applied as critical aerospace components, semiconductor packaging materials, and multifunctional coatings and adhesives. However, the brittle nature of epoxy resin leads to poor resistance to crack initiation and propagation, significantly hindering their applications as high-performance composites. Herein, we develop an architectured composite lattice with simultaneous high toughness and strength through a 3D printing technique. Strengthening and toughening zones possessing solid and highly ordered lattice structures, respectively, are rationally assembled into a layered structure. The resultant composite lattices deliver significantly improved flexural properties and crack resistance properties, exhibiting 400%, 83% and 36% higher toughness, specific strength, and fracture toughness than their solid counterpart, respectively. The exceptional strength and toughness of the composite lattices come from the synergetic effect of the strengthening and toughening zones, as confirmed by both experimental and theoretical analysis. The current findings provide an effective strategy for the fabrication epoxy-based composites with precisely controlled structures and mechanical performances.